2010
DOI: 10.2353/ajpath.2010.091109
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin-1 Receptor (NK1-R) Expression in the Brains of SIV-Infected Rhesus Macaques

Abstract: Recent studies suggest a link between neuropsychiatric disorders and HIV/SIV infection. Most evidence indicates that monocytes/macrophages are the primary cell type infected within the CNS and that they contribute to CNS inflammation and neurological disease. Substance P (SP), a pleotropic neuropeptide implicated in inflammation, depression, and immune modulation via interaction with its cognate receptor, the neurokinin 1 receptor (NK1-R), is produced by monocyte/macrophages. While the presence of NK1-R on neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Elevated levels of substance P have been observed in the serum of HIV infected patients and simian immunodeficiency virus-infected rhesus macaques (Douglas et al, 2001, 2008a,b; Lai et al, 2001; Vinet-Oliphant et al, 2010). Viral levels correlate with the amount of substance P released by immune cells and it has been suggested that this neuropeptide may facilitate viral replication by increasing the expression of receptors including CCR5 that are required for HIV infection of host cells (Bost, 2004a; Manak et al, 2010).…”
Section: Evidence For the Involvement Of Substance P In Cns Disordersmentioning
confidence: 99%
“…Elevated levels of substance P have been observed in the serum of HIV infected patients and simian immunodeficiency virus-infected rhesus macaques (Douglas et al, 2001, 2008a,b; Lai et al, 2001; Vinet-Oliphant et al, 2010). Viral levels correlate with the amount of substance P released by immune cells and it has been suggested that this neuropeptide may facilitate viral replication by increasing the expression of receptors including CCR5 that are required for HIV infection of host cells (Bost, 2004a; Manak et al, 2010).…”
Section: Evidence For the Involvement Of Substance P In Cns Disordersmentioning
confidence: 99%
“…Depressive symptoms have been associated with poor HIV-related outcomes, such as rapid progression of HIV disease, higher mortality rates, poor adherence to cART, and higher HIV viral loads (Evans et al, 2002; Horberg et al, 2008; Ickovics et al, 2001; E Shacham, Nurutdinova, Satyanarayana, Stamm, & Overton, 2009; Vinet-Oliphant et al, 2010). Depression has also been associated with high-risk behaviors: alcohol use in both HIV-infected and HIV-negative individuals (Sullivan, Goulet, Justice, & Fiellin, 2011) and illicit drug use (Berger-Greenstein et al, 2007; Bing et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Double-and triple-label confocal microscopy was performed to colocalize SIV RNA with cell type-specific markers to determine the immunophenotype of infected cells, as described previously (47 (24,28,34,47,50,51). After incubation with the primary antibodies (anti-CD3, anti-OPD4/CD45RO [which only detects CD45RO on CD4 ϩ T cells {34}], anti-CD68, anti-CD163, or anti-BrdU) and subsequent washes, the appropriate species-specific secondary antibodies were applied (Alexa Fluor 488-or 633-conjugated goat anti-rabbit or goat anti-mouse IgG1 or goat anti-rat [Invitrogen, Carlsbad, CA]).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue samples collected at biopsy or necropsy were fixed in Z-Fix (Anatech, Battle Creek, MI) and embedded in paraffin, and 5-m-thick sections were cut from select tissues and adhered to charged glass slides. SIV RNA in situ hybridization (ISH) was then performed, as described previously (24,28,47,48), using SIV RNA sense/antisense probes tagged with digoxigenin (DIG) and obtained from Lofstrand Laboratories (Gaithersburg, MD) or provided by Jake Estes (AIDS and Cancer Virus Program at the Frederick National Laboratory of Cancer Research) (49). The chromogens used were nitroblue tetrazolium (NBT)-5-bromo-4-chloro-3-indolylphosphate (BCIP) for light microscopy or liquid permanent red for fluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%